Representações do trabalho docente: qual a construção presente no discurso do futuro professor de língua portuguesa? - Spencer, Louise Cervo (2015)
This dissertation aimed to realize the construction of the relevant representations to the teaching presented by a student of degree in Letters. In order to reach this objective, we take into account the understanding that the teacher in formation is about the actions and activities involving this profession and the decision process that led him to attend a degree and following this career. Therefore, we chose to develop a longitudinal research from a qualitative analysis in order to understand the uniqueness of the individual respondent experiences. This study was under guidance of theoretical and methodological assumptions of Interacionism Sociodiscursivo (ISD) of Bronckart and Bronckart and Machado. The choice of this theory is due to the importance given by her to the study of the role of the practice of language (discursive act) in work situations, in this case specifically, the teaching work. The proposal of the ISD is to analyze (understand) the relationship between language and work (teaching). To think these relations, this work brought as a first action to conducting interviews, starting in 2011, with a new students in the same year, in Letters course of a University. Were held to total four interviews in specific moments graduation this student, namely: first semester (beginning of the course), third quarter (the period before to teaching disciplines and the internship), fifth semester (the period after to teaching disciplines and before the internship ) and eighth semester (period after the internship). From the generated text, we try to analyze them based on, first, the context of production followed the three levels proposed by ISD, namely the organization, the enunciation and semantic. The analysis allows us to answer our research questions and concluded: that social, predominant role in the texts, exercised by our interviewee was a graduate student; S13 understand that the teacher as the primary actant in teaching, establishing it as an actor, and students as an agent; that for the interviewee, the teacher's work is constituted as interpersonal, personal, sometimes impersonal and also interactional; we see that their perception of the profession is constantly accompanied by insecurity, despite having the certainty of desire to follow the teaching profession. So based on what we identified in the interviews, S13 represents the teaching as something pleasant and at the same time complex, as it requires both theoretical knowledge as knowledge of the human. Also, our interviewee understands that Obligatory curricular training becomes extremely important for teacher training as it is the time of training in which the student is connected directly to the practice, allowing reflect and reframe their actions.